PENINGKATAN KEMAMPUAN MENULIS PERMULAAN DENGAN MENGGUNAKAN METODE STRUKTUR ANALITIK SINTETIK (SAS) PADA PEMBELAJARAN BAHASA INDONESIA SISWA KELAS I UPT. SD NEGERI 20 BARINGIN - Nelnialis Nelnialis (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
The low ability of students to write at the beginning of the class, especially in Indonesian subjects, is still experienced by students of class I UPT. SD Negeri 20 Baringin because the teacher has not used a suitable method in writing, namely teaching writing only by asking students to follow the teacher's writing on the blackboard without any writing guidance from the teacher himself. Therefore, many students have difficulty in writing and students seem inactive in learning. The formulation of the problems in this study are, (1) How is the teacher's ability to manage learning by applying the Synthetic Analytical Structure (SAS) method in the writing material of the UPT class I students. SD Negeri 20 Baringin? (2) How do students' activities through the Synthetic Analytical Structures (SAS) method in the writing material of class I UPT students. SD Negeri 20 Baringin (3) How to improve students' initial writing skills through the Synthetic Analytical Structures (SAS) method in writing material for class I UPT students. SD Negeri 20 Baringin ?. The research method used was classroom action research (PTK). The research subjects were students of class I UPT. SD Negeri 20 Baringin, totaling 32 people. The ability to write at the beginning of the students had an increase in each indicator, namely, the indicator of neatness of writing in the first cycle with a percentage of 62.5% and increased in the second cycle with a percentage of 84.4%, the indicator of word completeness in the first cycle with a percentage of 34.4% and increased in the cycle. II with a percentage of 81.3% and indicators of word structure in the sentence in the first cycle with a percentage of 62.5% and increasing in the second cycle with a percentage of 87.5%. Overall the results of the research which lasted for the second cycle showed that the Synthetic Analytical Structures method could be applied to the pre-writing material. This is indicated by the ability of students to write at the beginning of each cycle, which has increased and is strengthened by the results of the research, the ability of teachers to increase in each cycle, namely in cycle I with a percentage of 75% and increasing in cycle II with a percentage of 96.15%, as well as student activities which also increased. increased in each cycle, namely in the first cycle with a percentage of 64.28% and increased in the second cycle with a percentage of 85.71%.